Pengaruh Model Pembelajaran Think Pair Share Menggunakan Media Google Classroom terhadap Kemampuan Komunikasi Matematis Mahasiswa IAIN Tulungagung - Nadya Alvi Rahma; Masithoh Yessi Rochayati; Muniri Muniri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
Mathematical communication skill is very important for university students because through communication, students can convey their mathematical ideas, knowledge and arguments. However, the facts show that the written mathematical communication skills of students majoring in Mathematics Education at IAIN Tulungagung are classified as low. The low written mathematical communication skill of students is indicated by errors in writing mathematical symbols on an equation and unsystematic writing of the steps to solve mathematical problems. This study aimed to determine the effectiveness of the Think Pair Share (TPS) learning model using Google Classroom media to improve the written mathematical communication skill of IAIN Tulungagung students. Several previous researchers have reviewed the use of Google Classroom in learning, but it was not integrated with the TPS learning model and did not focus on the influence on students' mathematical communication skill. The study sample was 40 students of the 5th semester in 2019/2020 academic year majoring in Mathematics Education at IAIN Tulungagung who took the Differential Equation course. The data collection was carried out by providing a pretest and posttest before and after implementing the learning using the TPS model with Google Classroom media. Then, the data from the pretest and posttest results were analyzed using the Wilcoxon test because the data were not normally distributed. The results of this study showed that the TPS learning model using Google Classroom media could improve the students' mathematical communication skill.